2009
DOI: 10.1590/s1676-06032009000400003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of riparian vegetation on the structure of the marginal aquatic habitat and the associated fish assemblage in a tropical Brazilian reservoir

Abstract: Effects of riparian vegetation removal on the structure of the marginal aquatic habitat and the associated fish fauna in a tropical Brazilian reservoir. Biotra Neotrop., 9(4): http://www.biotaneotropica.org.br/v9n4/en/abstract?article+bn00709042009.Abstract: Riparian zones represent areas of strong biological, physical and chemical interaction between terrestrial and aquatic ecosystems. These areas are usually typified by high diversity of fauna, flora and environmental processes. The present study evaluates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 14 publications
0
13
0
4
Order By: Relevance
“…Riparian zones represent areas of strong biological, physical and chemical interaction between terrestrial and aquatic ecosystems. Habitat structure is more diverse in sites where natural riparian vegetation is present (BELTRÃO et al 2009). Water shaded by riparian trees is cooler and contains more dissolved oxygen; roots of riparian vegetation provide spawning sites for fish and the associated invertebrates are a significant food resource for them (HARPER et al 1995); however, too dense a tree cover completely eliminates submerged macrophytes and hence other aquatic biota associated with them.…”
Section: Discussionmentioning
confidence: 99%
“…Riparian zones represent areas of strong biological, physical and chemical interaction between terrestrial and aquatic ecosystems. Habitat structure is more diverse in sites where natural riparian vegetation is present (BELTRÃO et al 2009). Water shaded by riparian trees is cooler and contains more dissolved oxygen; roots of riparian vegetation provide spawning sites for fish and the associated invertebrates are a significant food resource for them (HARPER et al 1995); however, too dense a tree cover completely eliminates submerged macrophytes and hence other aquatic biota associated with them.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors reported the importance of the interaction between the water body and the ground (Beltrão et al, 2009;Kobayashi et al, 2010;Salemi et al, 2012). This interaction is considered relevant to the aquatic environment because provide nutrients, organic matter, minerals and pollutants and as can modulate other variables as light and temperature (Falkenmark, 2011;Tsatsaros et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Precipitation is higher between April and June, with an annual average of 1095.9 mm (Rodal et al, 1998). Maximum altitudes in the area range between 650 and 1000 m (Beltrão et al, 2005) and average annual temperatures are 25 ºC. The vegetation in the area is the Caatinga/Agreste, a mostly deciduous open forest (Beltrão et al, 2005).…”
Section: Study Areamentioning
confidence: 99%
“…Maximum altitudes in the area range between 650 and 1000 m (Beltrão et al, 2005) and average annual temperatures are 25 ºC. The vegetation in the area is the Caatinga/Agreste, a mostly deciduous open forest (Beltrão et al, 2005). At each river reach, three subsamples of 40 x 40 x 2.5 cm of sediment were randomly taken using a D-shaped net (40 cm wide and 250 μm mesh).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation